2020
DOI: 10.5173/ceju.2020.0148
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and complications of Hyperthermic IntraVesical Chemotherapy using Mitomycin-C or Epirubicin for patients with non-muscle invasive bladder cancer after Bacillus Calmette-Guérin treatment failure

Abstract: Introduction Chemohyperthermia is a feasible option in BCG (bacillus Calmette-Guérin) failure patients who desire bladder preservation. We aimed to assess outcomes and complications of chemohyperthermia using mitomycin C (MMC) or epirubicin (EPI). Material and methods From March 2017 to February 2020, 103 BCG failure or intolerance patients with high-risk NMIBC (non-muscle invasive bladder cancer) underwent a hyperthermic intravesical chemotherapy (HIVEC) regimen. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…It is important to note that 38% of the patients in our group received only induction treatment without maintenance. Additionally, we included patients with CIS as a prognostic factor, which has been shown to be associated with a poorer response in patients with NMIBC failing after BCG [ 15 ]. Both variables (use of maintenance and presence of CIS) adversely correlated with survival without a HR recurrence in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that 38% of the patients in our group received only induction treatment without maintenance. Additionally, we included patients with CIS as a prognostic factor, which has been shown to be associated with a poorer response in patients with NMIBC failing after BCG [ 15 ]. Both variables (use of maintenance and presence of CIS) adversely correlated with survival without a HR recurrence in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since January 2020, only epirubicin has been utilized. According to the available data, the synergistic effect of a drug (chemotherapy and hyperthermia) was found to be comparable between epirubicin and MMC, both on an experimental and clinical level [ 14 , 15 ]. All instillations were performed with the CombatBRSsystem V2.0 (Combat Medical, Wheathampstead, UK).…”
Section: Study Population Characteristic and Methodsmentioning
confidence: 99%
“…Considering that this NMA focuses on HIVEC with MMC, it puts forward a new perspective: explore the combination of hyperthermia and other chemotherapeutic drugs instead of MMC. It has been found that using MMC or EPI in HIVEC did not influence the response to treatment (p = 0.157) (52). For example, one study found that the therapeutic rank of GEM was superior to that of BCG in their network model (53).…”
Section: Discussionmentioning
confidence: 99%
“…However, fewer than half completed the cycle of full-dose BCG treatment because of adverse complications (Kulkarni et al, 2007). Subsequently, various treatments were explored, such as new drugs, radiation therapy, and novel chemotherapy approaches including intravenous chemotherapy, IAC and hyperthermic intravesical chemotherapy (Chiancone et al, 2020;Di Lorenzo et al, 2010;Weiss et al, 2006;Yang et al, 2017). The IAC had received attention because of higher chemotherapy concentration in the bladder and lower systemic toxicity compared with intravenous chemotherapy (Eapen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%